Morphology and biology of globoid leaf gall induced by a cecidomyiidae (Diptera) on Neltuma caldenia (Fabaceae) in the Province of La Pampa (Semiárida, 2023)
The caldén is an arboreal species of tempered-semiarid environments and endemic to Argentina. The objective of the work was to study the morphology, development, and biology of the gall induced by a cecidomyiid on the caldén leaf. Leaves with and without galls were collected in fragments of peri-urban forests in Santa Rosa, La Pampa. The temporary histological sections were made by freehand and permanent histological sections with a microtome. The larvae, pupae, and adults of the inducer were examined. Gall formation alters the zone of the leaf base and the petiole, mainly the primary pulvinus. The gall is globoid, closed, yellow-brown when mature, with 1-3 larval chambers, and made up of two parts (upper and lower). The internal organization in tissue compartments is consistent with the general structure of the cecidomyiids gall. The distinctive features are the cork formation, the modification of the epidermal cells in sclereids in the contact zone between the two parts, and the dehiscence. The inducer is a univoltine cecidomyiid species that completes the life cycle in one year, from spring to spring, and it survives the winter season inside the gall as a mature larva.
Keywords: insect gall; Cecidomyiidae; caldén; Prosopis